Environmental regulation and green productivity of the construction industry in China. Issue 2 (11th September 2020) - Zhang, Jingxiao; Pu, Si; Philbin, Simon P; Li, Hui; Skitmore, Martin; Ballesteros-Pérez, Pablo
Abstract : There are few studies analysing whether different types of environmental regulation have differential impacts on the efficiency of the construction industry. Using 2012–2016 panel data from 30 provinces in China, the green total factor productivity (GTFP) of the construction industry is measured with a global Malmquist–Luenberger productivity index based on the epsilon measure model. Thereafter, a panel tobit regression model is proposed to explore the relationship between three types of environmental regulation and the GTFP of the construction industry. The results show that ( a ) from 2012 to 2016, the GTFP of the Chinese construction industry grew slowly at an average annual rate of 0.14%; ( b ) both one-phase lagged command-and-control and current phase market-based environmental regulation had a positive linear relationship with GTFP, while one-phase lagged voluntary environmental regulation, on the other hand, had an inverted U-shaped relationship with GTFP; ( c ) the three types of environmental regulation can be combined to establish a suitable environmental regulation system. The findings of this study provide guidance for the sustainable development of the construction industry by combining the actions of different types of environmental regulation.